INVESTIGATING THE IMPACT OF LASER POWER AND SCAN SPEED ON ENGRAVING ASPEN THERMOWOOD (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This study examines the effect of pre-heat treatment on laser engraving of aspen thermowood. We used an infrared CO2 laser with a wavelength of 10640 nm to engrave aspen thermowood samples with different pre-treatment temperatures, including one non-treated sample (base). The samples had a similar moisture content of about 6 - 8%, but exhibited different shades of brown depending on the pre-treatment temperature. The engraving depth and width were measured for each sample, and 8 graphs were constructed to analyze the results. Our findings show that pre-treatment temperature has a significant effect on the efficiency of laser engraving, with higher pre-treatment temperatures resulting in deeper engraving lines. The study provides valuable insights into the optimization of laser engraving parameters for aspen thermowood, and demonstrates the potential of pre-heat treatment to improve the quality of laser-engraved wooden products.